Rheumatic heart disease burden, trends, and inequalities in the Americas, 1990–2017: a population-based study. Issue 10 (October 2019) - Ordunez, Pedro; Martinez, Ramon; Soliz, Patricia; Giraldo, Gloria; Mujica, Oscar J; Nordet, Porfirio
Summary: Background: The World Health Assembly 2018 approved a resolution on rheumatic heart disease to strengthen programmes in countries where this condition remains a substantial public health problem. We aimed to describe the regional burden, trends, and inequalities of rheumatic heart disease in the Americas. Methods: In this secondary analysis of the Global Burden of Disease, Injuries, and Risk Factors Study (GBD) 2017, we extracted data for deaths, prevalence of cases, disability-adjusted life-years (DALYs), years lived with disability, and years of life lost (YLL) as measures of rheumatic heart disease burden using the GBD Results Tool. We analysed 1990–2017 trends in rheumatic heart disease mortality and prevalence, quantified cross-country inequalities in rheumatic heart disease mortality, and classified countries according to rheumatic heart disease mortality in 2017 and 1990–2017. Findings: GBD 2017 estimated that 3 604 800 cases of rheumatic heart disease occurred overall in the Americas in 2017, with 22 437 deaths. We showed that in 2017 rheumatic heart disease mortality in the Americas was 51% (95% UI 44–59) lower (1·8 deaths per 100 000 population [95% uncertainty interval 1·7–1·9] vs 3·7 deaths per 100 000 population [3·4–3·9]) and prevalence was 30% (29–33) lower (346·4 cases per 100 000 [334·1–359·2] vs 500·6 cases per 100 000 [482·9–519·7]) than the corresponding global estimates. DALYs were half of those globally (55·7 per 100 000 [49·8–63·5] vs 118·7 per 100 000 [108·5 to 130·7]), with a 70% contribution from YLL (39·1 out of 55·7 per 100 000). A significant reduction in rheumatic heart disease mortality occurred, from a regional average of 88·4 YLL per 100 000 (95% uncertainty interval 88·2–88·6) in 1990 to 38·2 (38·1–38·4) in 2017, and a significant reduction in income-related inequality, from an excess of 191·7 YLL per 100 000 (68·6–314·8) between the poorest and richest countries in 1990 to 66·8 YLL per 100 000 (6·4–127·2) in 2017. Of the 37 countries studied, eight (22%) had both the highest level of premature rheumatic heart disease mortality in 2017 and the smallest reduction in this mortality between 1990 and 2017. Interpretation: The Americas have greatly reduced premature mortality due to rheumatic heart disease since 1990. These health gains were paired with a substantial reduction in the magnitude of income-related inequalities across countries, which is consistent with overall socioeconomic and health improvements observed in the Region. Countries with less favourable rheumatic heart disease situations should be targeted for strengthening of their national programmes. Funding: None.